2015
DOI: 10.1002/cite.201400126
|View full text |Cite
|
Sign up to set email alerts
|

Experimentelle Untersuchung zur Foulingneigung einer Polymerdispersion auf modifizierten Oberflächen

Abstract: Bei der Herstellung und Verarbeitung von Polymerdispersionen ist Fouling, also die unerwünschte Belagbildung auf Oberflächen in Wärmeübertragern und Reaktoren, ein zentrales Problem für die ökonomische und ökologische Effizienz. In dieser Studie wird das Foulingverhalten von Polymerdispersionen auf beheizten und gekühlten Oberflächen untersucht. Dabei wird die Foulingneigung auf Wärmeübertragern in Abhängigkeit von betrieblichen (Wärmestromdichte, Fluidtemperatur, Feststoffkonzentration, Strömungsregime) und a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
1
8
0
1
Order By: Relevance
“…The craters have a diameter up to 100 µm and are visible even without magnification. Such a structure was also found by Gottschalk et al9 during polymer fouling experiments on different heated surfaces. Since the boiling temperature of the polymer dispersion with 100 °C is far above the wall temperature, this structure cannot result from an evaporation process forming bubbles.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The craters have a diameter up to 100 µm and are visible even without magnification. Such a structure was also found by Gottschalk et al9 during polymer fouling experiments on different heated surfaces. Since the boiling temperature of the polymer dispersion with 100 °C is far above the wall temperature, this structure cannot result from an evaporation process forming bubbles.…”
Section: Resultssupporting
confidence: 82%
“…They demonstrated that reactor orientation and flow direction have a significant effect on fouling behavior. Gottschalk et al9 carried out initial investigations of a vinyl acetate based copolymer. It was shown that fouling can be reduced by modifying the surface with diamond‐like carbon (DLC) coatings.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the practical importance of fouling in emulsion polymerization reactors, the topic has only been scarcely treated in literature. It has been reported that fouling can be reduced by modifying the surface of the reactor . In the absence of polymerization (particulate fouling), fouling increased as the stability of the latex decreased and the solids content and the temperature increased.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that fouling can be reduced by modifying the surface of the reactor. 16 In the absence of polymerization (particulate fouling), fouling increased as the stability of the latex decreased and the solids content and the temperature increased. Furthermore, the distribution of fouling in the reactor depended on the flow patterns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cunningham und O'Driscoll [6] untersuchten Betriebsfenster, in denen während der Polymerisation von Methylmethacrylat (MMA) in einem Rohrreaktor Fouling auftritt. Gottschalk et al [7] führten erste Untersuchungen mit einem Copolymer auf Vinylacetatbasis durch. Es konnte gezeigt werden, dass es möglich ist, Verschmutzungen durch die Modifizierung der Oberfläche mit diamantähnlichen Kohlenstoffbeschichtungen (diamond-like carbon, DLC) zu reduzieren.…”
Section: Introductionunclassified